Towards a better understanding of adult idiopathic epidermal necrolysis: a retrospective study of 19 cases. (5th June 2021) - Monnet, P.; Rodriguez, C.; Gaudin, O.; Cirotteau, P.; Papouin, B.; Dereure, O.; Tetart, F.; Lalevee, S.; Colin, A.; Lebrun‐Vignes, B.; Abe, E.; Alvarez, J.‐C.; et al.
Abstract: Background: Most cases of Stevens–Johnson syndrome and toxic epidermal necrolysis are drug‐induced. A small subset of cases remain with unknown aetiology (idiopathic epidermal necrolysis [IEN]). Objective: We sought to better describe adult IEN and understand the aetiology. Methods: This retrospective study was conducted in 4 centres of the French national reference centre for epidermal necrolysis. Clinical data were collected for the 19 adults hospitalized for IEN between January 2015 and December 2019. Wide toxicology analysis of blood samples was performed. Histology of IEN cases was compared with blinding to skin biopsies of drug‐induced EN (DIEN, 'controls'). Available baseline skin biopsies were analysed by shotgun metagenomics and transcriptomics and compared to controls. Results: IEN cases represented 15.6% of all EN cases in these centres. The median age of patients was 38 (range 16–51) years; 68.4% were women. Overall, 63.2% ( n = 12) of cases required intensive care unit admission and 15.8% ( n = 3) died at the acute phase. Histology showed the same patterns of early‐ to late‐stage EN with no difference between DIEN and IEN cases. One toxicology analysis showed unexpected traces of carbamazepine; results for other cases were negative. Metagenomics analysis revealed no unexpected pathological microorganism. Transcriptomic analysis highlighted a different pro‐apoptotic pathway in IEN compared to DIEN, with an overexpression of apoptosis effectors TWEAK/TRAIL. Conclusions: IEN affects young people and is a severe form of EN. A large toxicologic investigation is warranted. Different pathways seem involved in IEN and DIEN, leading to the same apoptotic effect, but the primary trigger remains unknown.